2008
DOI: 10.1039/b716910h
|View full text |Cite
|
Sign up to set email alerts
|

Controlling cis/trans-selectivity in intramolecular Diels–Alder reactions of benzo-tethered, ester linked 1,3,9-decatrienes

Abstract: Predictions from DFT (B3LYP/6-31 G(d))-computed stereoisomer product distributions for intramolecular Diels-Alder (IMDA) reactions have been successfully replicated in the laboratory. Benzo-tethered hexadienyl acrylates generally undergo moderately trans-selective IMDA reactions which, as suggested by DFT calculation, arise from two opposing transition structure (TS) features: stabilising secondary orbital interactions, which are stronger in the cis-TSs, and stabilising pi-conjugative interactions between the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2008
2008
2011
2011

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 45 publications
0
12
0
Order By: Relevance
“…These markedly different dihedral angles between the aromatic ring and the C3C4 double bond in the cis ‐ and trans ‐IMDA TSs of 10 suggest that placement of a large group at either C3 or C12 should disfavor the trans ‐TS relative to the cis ‐TS. Both DFT calculations and experimental findings confirmed this expectation: both Br and trimethylsilyl (TMS) substituents at C3 or C12 led to very high cis ‐IMDA selectivities (>95 % cis ) (Scheme ) 16…”
Section: Methodsmentioning
confidence: 68%
See 3 more Smart Citations
“…These markedly different dihedral angles between the aromatic ring and the C3C4 double bond in the cis ‐ and trans ‐IMDA TSs of 10 suggest that placement of a large group at either C3 or C12 should disfavor the trans ‐TS relative to the cis ‐TS. Both DFT calculations and experimental findings confirmed this expectation: both Br and trimethylsilyl (TMS) substituents at C3 or C12 led to very high cis ‐IMDA selectivities (>95 % cis ) (Scheme ) 16…”
Section: Methodsmentioning
confidence: 68%
“…Recently, we explored the cis / trans selectivity in IMDA reactions of a series of hexadienyl acrylates 15. 16 Interestingly, we observed that, whereas the IMDA reaction of the cognate system possessing the ethylene tether (CH 2 CH 2 OC(=O)) displays strong cis stereoselectivity, the IMDA reactions of the benzo‐tethered systems exhibit moderate trans selectivity, for example, cis / trans =26:74 (Scheme ) 15…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…This goal remains elusive, notwithstanding recent significant progress towards delineating the various factors controlling IMDA stereochemistry. [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] In this paper, we explore, using density functional theory, the origin of cis/trans selectivity in IMDAs of 1,3,8nonatrienes, 1-9, possessing tethers that are three atoms long (Scheme 1). Given the experimental fact that IMDAs generally give kinetically controlled product distributions, the key to understanding cis/trans selectivity in these reac-Abstract: Intramolecular Diels-Alder (IMDA) transition structures (TSs) and energies have been computed at the B3LYP/6-31+G(d) and CBS-QB3 levels of theory for a series of 1,3,8nonatrienes, H 2 C=CH À CH=CH À CH 2 À X À Z À CH=CH 2 [ À X À Z À = À CH 2 À CH 2 À (1); À O À C(=O) À (2); À CH 2 À C(=O) À (3); À O À CH 2 À (4); À NH À C(=O) À (5); ÀSÀC(=O)À (6); ÀOÀC(=S)À (7); ÀNHÀC(=S)À (8); ÀSÀC(=S)À (9)].…”
Section: Introductionmentioning
confidence: 99%